Artificial meniscus and method of manufacturing the same

CN122998467APending Publication Date: 2026-10-30ZHONGJIE CHAORUN (TIANJIN) MEDICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610937882.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]为了解决上述技术问题,本申请提供一种人工半月板的制造方法及由该方法制成的人工半月板,以至少缓解上述技术问题

Benefits of technology

[0037]本申请的人工半月板制造方法,针对传统单一基材制造方案难以平衡力学性能与弹性、耐疲劳性能差的技术缺陷,通过步骤一合成特定分子量的增强水性聚酯,为后续形成双分子缠结结构奠定基础。相较于传统方案中直接采用商用单一基材,本申请通过调控多元醇比例、反应温度及去离子水添加速度等关键参数,精准控制聚酯分子的数均分子量在5000-20000范围内,使其既具备良好的力学增强特性,又能与多羟基醇大分子形成有效缠结,从分子结构层面解决了单一材料性能失衡的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998467A_ABST
    Figure CN122998467A_ABST
Patent Text Reader

Abstract

The application provides an artificial meniscus and a manufacturing method thereof, and the method comprises the following steps: placing polyols, isocyanate and a catalyst in a reaction container, and stirring and reacting under temperature rising; adding a solvent to react with 2,2-dimethylol propionic acid, and then adding a solvent to react with triethylamine; adding deionized water and adjusting the stirring speed, and finally removing the solvent to obtain an aqueous polyester; dissolving polyhydroxy alcohol macromolecules in deionized water to form a transparent solution, mixing the transparent solution with the aqueous polyester, and performing pre-mixing, fine mixing and high-temperature and high-pressure treatment to obtain a pre-crosslinking fluid; heating the pre-crosslinking fluid to form a gel fluid, injecting the gel fluid into a preheated mold, taking out the preliminarily formed artificial meniscus after cooling, and performing freezing, drying and hydration treatment on the preliminarily formed artificial meniscus to obtain an enhanced artificial meniscus. The application can make the manufactured artificial meniscus have good mechanical bearing capacity, elasticity and fatigue resistance, and can meet the use requirements of long-term implantation in clinic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of artificial implant technology, and more specifically, to an artificial meniscus and a method for manufacturing the same. Background Technology

[0002] As a crucial cushioning and stabilizing structure within the knee joint, the meniscus, if damaged and unable to be effectively repaired, will lead to accelerated wear and tear of the articular cartilage, subsequently causing degenerative osteoarthritis and severely impacting patients' joint function and quality of life. Therefore, the research and application of artificial menisci are of significant clinical importance for meniscus repair. The core requirement is to balance mechanical load-bearing capacity, fatigue resistance, and biocompatibility to effectively replace the function of the original meniscus.

[0003] In existing artificial meniscus manufacturing methods, a single polymer material is typically used for molding or 3D printing. This method first selects a single substrate such as polycarbonate, polyurethane, or collagen, melts or dissolves it, and then injects it into a mold; subsequently, it is shaped by cooling at room temperature or photocuring; finally, the finished product is obtained after simple grinding and polishing.

[0004] However, this traditional manufacturing method has obvious technical defects. It is difficult to balance the mechanical strength and elasticity requirements with a single substrate, resulting in products that are either too hard and easily damage cartilage, or have insufficient mechanical load-bearing capacity and poor fatigue resistance. At the same time, the lack of precise control over the molecular chain structure during the molding process makes it easy for bubbles to form inside the material and for uneven molecular distribution to form, which further reduces the mechanical stability and service life of the product and cannot meet the clinical needs of long-term implantation of artificial menisci. Summary of the Invention

[0005] To address the aforementioned technical problems, this application provides a method for manufacturing an artificial meniscus and an artificial meniscus made by the method, thereby at least alleviating the aforementioned technical problems.

[0006] A method for manufacturing an artificial meniscus includes the following steps:

[0007] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0008] Polyol, isocyanate and catalyst were placed in a reaction vessel and heated and stirred to react; solvent was added to react with 2,2-dimethylolpropionic acid, and then solvent was added to react with triethylamine; deionized water was added and the stirring speed was adjusted, and finally the solvent was removed to obtain waterborne polyester;

[0009] Step 2: Preparation of fatigue-resistant hydrogel pre-crosslinked fluid

[0010] Polyhydroxy alcohol macromolecules are dissolved in deionized water to form a transparent solution, which is then mixed with the aqueous polyester from step one. After premixing, fine mixing and high temperature and high pressure treatment, a pre-crosslinked fluid is obtained.

[0011] Step 3: Integrated molding of artificial meniscus

[0012] The pre-crosslinked fluid is heated to form a gel fluid, which is then injected into a preheated mold. After cooling, the pre-formed artificial meniscus is removed.

[0013] Step 4: Artificial Meniscus Reinforcement

[0014] The pre-formed artificial meniscus is freeze-dried and hydrated to obtain an enhanced artificial meniscus.

[0015] Optionally, the mass ratio of polypropylene glycol (PPG) to polyethylene glycol (PEG) is 1:1.2-1.5.

[0016] Optionally, the peristaltic pump adds deionized water at a rate of 5-10 mL / min.

[0017] Optionally, the amount of triethylamine (TEA) added is 2-4 mL.

[0018] Optionally, the number-average molecular weight of the polyester molecules is 5,000-20,000.

[0019] Optionally, the stepwise stirring method specifically involves: first, placing the system in an environment of 50~60℃ and mechanically stirring at a speed not exceeding 80r / min.

[0020] Optionally, the molecular weight of the polyhydroxy alcohol macromolecular polyvinyl alcohol is 70,000-80,000.

[0021] Optionally, the temperature difference between the gel fluid and the meniscus mold is 5~10℃.

[0022] Optionally, the pressing pressure of the pressing head device is 0.3-0.5 MPa.

[0023] Optionally, the overnight freezing time is 12-16 hours.

[0024] Optionally, the amount of stannous octoate added is 0.1-0.3g.

[0025] Optionally, the fine mixing time is 30-45 minutes.

[0026] Optionally, the mold is made of polytetrafluoroethylene.

[0027] Optionally, the vacuum degree of the vacuum drying oven is -0.09 to -0.08 MPa.

[0028] Optionally, the molecular weight of the polypropylene glycol (PPG) is 2000-3000, and the molecular weight of the polyethylene glycol (PEG) is 1000-2000.

[0029] Optionally, the mass ratio of the aqueous polyester to the polyhydroxy alcohol transparent solution is 1:6-10.

[0030] Optionally, the polyol includes polypropylene glycol (PPG) and polyethylene glycol (PEG); the isocyanate is IPDI, and the addition amount is 5-12g; the catalyst is stannous octoate; and the solvent is acetone.

[0031] Optionally, the temperature is raised to 70~80℃, the stirring speed is 100~200r / min, and the reaction is continued for 2~3 hours; acetone and 2,2-dimethylolpropionic acid (3-5g) are added and reacted for 1~2 hours, then acetone and triethylamine are added and reacted at 40~50℃ for 30 minutes; when adding deionized water, the stirring speed is increased to 300~500r / min, and finally the acetone is removed by vacuum filtration.

[0032] Optionally, the polyhydroxy alcohol macromolecule is polyvinyl alcohol, with an addition amount of 30-50g, dissolved in 50-100mL of deionized water at 120℃ and 103KPa; the amount of waterborne polyester added is 5-10g; the high temperature and high pressure treatment conditions are 120℃ and 103KPa, maintained for 20-30 minutes.

[0033] Optionally, the pre-crosslinked fluid is heated to 70~80℃ to form a gel fluid, and the mold is preheated to 60~70℃; the gel fluid is injected into the mold through the pressing head device, and the pressing is stopped when gel seeps out from the mold vent hole.

[0034] Optionally, the freezing temperature is -20℃, the drying is vacuum drying at 35~40℃ for 18~20 hours, and the hydration treatment is soaking in deionized water for more than 12 hours.

[0035] An artificial meniscus, made by any of the above manufacturing methods.

[0036] Technical advantages of the technical solution provided in this application

[0037] This application's method for manufacturing artificial menisci addresses the technical shortcomings of traditional single-substrate manufacturing methods, which struggle to balance mechanical properties with elasticity and poor fatigue resistance. By synthesizing a specific molecular weight reinforced waterborne polyester in step one, it lays the foundation for subsequent formation of a bimolecular entangled structure. Compared to traditional methods that directly use commercially available single-substrate materials, this application precisely controls the number-average molecular weight of the polyester molecules within the range of 5000-20000 by adjusting key parameters such as the polyol ratio, reaction temperature, and deionized water addition rate. This ensures that the polyester possesses both excellent mechanical reinforcement properties and the ability to form effective entanglement with polyol macromolecules, thus solving the problem of performance imbalance in single-material manufacturing at the molecular structure level.

[0038] By employing premixing, fine mixing, and high-temperature, high-pressure treatment in step two, a bimolecularly entangled hydrogel pre-crosslinked fluid is constructed, solving the problems of uneven molecular distribution and poor structural stability within the material in traditional solutions. Traditional solutions rely solely on simple mixing or melt molding, making it difficult for molecular chains to form an ordered bond. In contrast, this application utilizes step-by-step stirring control (low-speed premixing to avoid bubble generation, and high-temperature fine mixing to promote molecular chain de-entanglement and entanglement), followed by high-temperature, high-pressure treatment at 120℃ and 103KPa, to form a uniform and dense entangled network between the waterborne polyester and polyvinyl alcohol molecular chains. Compared to traditional materials, this structure significantly improves the mechanical strength and fatigue resistance of the hydrogel.

[0039] Step three employs a precise temperature-controlled integrated molding process, maintaining the temperature difference between the gel fluid and the mold within 5-10°C. Quantitative injection via a pressure head device solves the problems of air bubbles and low molding accuracy inherent in traditional molding processes. Traditional mold molding often results in uneven material shrinkage due to excessive temperature gradients. However, the temperature difference control and pressure injection method of this application ensures uniform flow and full filling of the gel fluid within the mold, reducing internal defects and improving the product's molding accuracy and structural consistency, resulting in an artificial meniscus that more closely resembles the original anatomical structure.

[0040] Step four involves a freeze-drying-hydration enhancement process to further strengthen the molecular entanglement effect, addressing the issues of insufficient mechanical stability and short service life in traditional products. The freezing process makes the molecular chains more tightly arranged, vacuum drying removes free water and fixes the entangled structure, and the hydration treatment forms a stable hydrogel network. Compared to traditional products that are used directly after molding, this enhancement process significantly improves the compressive stability and abrasion resistance of the artificial meniscus, enabling it to better withstand the long-term repetitive mechanical loads on the knee joint. Attached Figure Description

[0041] Figure 1 This is a schematic flowchart of a method for manufacturing an artificial meniscus according to an embodiment of this application;

[0042] Figure 2Here are scanning electron microscope images of bimolecular entangled gels from embodiments of this application;

[0043] Figure 3 This is a polyester molecular weight test curve for an embodiment of this application;

[0044] Figure 4 This is a chromatogram of triethylamine and acetone residue tests in an example of this application;

[0045] Figure 5 This is a comparison diagram of the compressive stability of the artificial meniscus before and after fatigue in an embodiment of this application;

[0046] Figure 6 This is a curve showing the change in the friction coefficient of the artificial meniscus as a function of the number of friction cycles in an embodiment of this application. Detailed Implementation

[0047] like Figure 1 The image shows a method for manufacturing an artificial meniscus according to an embodiment of this application, comprising the following steps:

[0048] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0049] Polyol, isocyanate and catalyst were placed in a reaction vessel and heated and stirred to react; solvent was added to react with 2,2-dimethylolpropionic acid, and then solvent was added to react with triethylamine; deionized water was added and the stirring speed was adjusted, and finally the solvent was removed to obtain waterborne polyester;

[0050] Step 2: Preparation of fatigue-resistant hydrogel pre-crosslinked fluid

[0051] Polyhydroxy alcohol macromolecules are dissolved in deionized water to form a transparent solution, which is then mixed with the aqueous polyester from step one. After premixing, fine mixing and high temperature and high pressure treatment, a pre-crosslinked fluid is obtained.

[0052] Step 3: Integrated molding of artificial meniscus

[0053] The pre-crosslinked fluid is heated to form a gel fluid, which is then injected into a preheated mold. After cooling, the pre-formed artificial meniscus is removed.

[0054] Step 4: Artificial Meniscus Reinforcement

[0055] The pre-formed artificial meniscus is freeze-dried and hydrated to obtain an enhanced artificial meniscus.

[0056] The present invention will be described in detail below with reference to embodiments, aiming to fully disclose the details of the solution from the technical essence.

[0057] Example 1

[0058] A method for manufacturing an artificial meniscus includes the following steps:

[0059] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0060] The core objective of this step is to prepare an aqueous polyester with a specific linear structure and molecular weight, laying the foundation for effective entanglement with polyvinyl alcohol in the subsequent process. The specific steps are as follows:

[0061] Weigh out 10g of polypropylene glycol (PPG, molecular weight 2000), 12g of polyethylene glycol (PEG, molecular weight 1000), 8g of isocyanate (IPDI), and 0.2g of stannous octoate, and place the above raw materials in a three-necked flask. The technical consideration for choosing this raw material ratio is that the mass ratio of PPG to PEG is 1:1.2. Orthogonal experiments have verified that this ratio can balance the linearity and hydrophilicity of polyester, avoiding the influence of excessive or weak hydrophilicity on the subsequent mixing and entanglement with polyvinyl alcohol. Stannous octoate, as a catalyst, is added at a controlled amount of 0.2g to ensure that the polymerization reaction proceeds gently and avoids excessive local reaction leading to molecular chain crosslinking.

[0062] The three-necked flask was placed in an oil bath and heated to 75°C. Mechanical stirring was carried out at 150 rpm for 2.5 hours. The technical reason for controlling this temperature and stirring speed is that 75°C is the optimal temperature for the reaction of IPDI and polyols, ensuring the reaction rate while avoiding side reactions caused by excessively high temperatures. The stirring speed of 150 rpm ensures uniform mixing of the raw materials, preventing localized high concentrations that could lead to molecular chain aggregation.

[0063] After the initial stage of the reaction, 12 mL of acetone was added to the flask, and after stirring thoroughly, 4 g of 2,2-dimethylolpropionic acid (DMPA) was added, and the reaction continued for 1.5 hours. The purpose of adding acetone is to adjust the viscosity of the system and provide conditions for the uniform dispersion of DMPA. As a hydrophilic functional monomer, the addition of 4 g of DMPA can introduce carboxyl groups into the polyester molecular chain, improve the water solubility of the polyester, and create conditions for subsequent mixing with polyvinyl alcohol aqueous solution.

[0064] A second system adjustment was then performed by adding 12 mL of acetone and 3 mL of triethylamine (TEA), and reacting at 45°C for 30 minutes. The role of triethylamine is to neutralize the carboxyl groups introduced by DMPA, further improving the water solubility and stability of the polyester. Experiments have verified that the addition of 3 mL can achieve complete neutralization without causing the system pH to become too high due to excess. The reaction temperature of 45°C can prevent the volatilization of triethylamine and ensure that the neutralization reaction proceeds fully.

[0065] After the reaction was complete, heating was stopped, and deionized water was added to the flask at a rate of 7 mL / min using a peristaltic pump. During this process, 8 mL of acetone was added for the third time, while the stirring speed was increased to 400 rpm. Controlling the deionized water addition rate to 7 mL / min is a key technical point in this step. Extensive experimental verification has shown that this rate can precisely terminate the polymerization reaction, avoiding excessively short molecular chains (molecular weight below 5000) due to excessively rapid addition or excessively long molecular chains (molecular weight above 20000) due to excessively slow addition, ultimately yielding a linear aqueous polyester with a number average molecular weight of 12000. Increasing the stirring speed to 400 rpm promotes system dispersion and prevents polyester molecule aggregation. The third addition of acetone further adjusts the viscosity, ensuring system homogeneity. Finally, acetone is removed by vacuum filtration to obtain a pure linear aqueous polyester.

[0066] Step 2: Preparation of fatigue-resistant hydrogel pre-crosslinked fluid

[0067] The core of this step is to achieve full entanglement of the molecular chains of waterborne polyester and polyvinyl alcohol through a stepwise mixing process, forming a stable and fluid pre-crosslinked fluid. The specific operation is as follows:

[0068] Accurately weigh 40g of polyvinyl alcohol with a molecular weight of 75,000 and place it in a high-pressure reactor. Dissolve it in 75mL of deionized water at 120℃ and 103KPa. After maintaining the temperature for 30 minutes, cool to room temperature to form a uniform and transparent aqueous solution of polyvinyl alcohol. Polyvinyl alcohol with a molecular weight of 75,000 was chosen because its molecular chain length best matches that of the aqueous polyester (molecular weight 12,000) prepared in step one, allowing for the formation of a dense entangled network. The high temperature and high pressure conditions of 120℃ and 103KPa accelerate the dissolution of polyvinyl alcohol, avoiding uneven mixing due to insufficient dissolution.

[0069] Weigh 7g of the aqueous polyester prepared in step one and add it to the above-mentioned polyvinyl alcohol aqueous solution at room temperature. At this time, the mass ratio of aqueous polyester to polyvinyl alcohol aqueous solution is 1:8. This ratio was determined through experimental optimization to ensure sufficient contact between the molecular chains of the two polymer materials. This avoids both the increase in system brittleness due to excessive aqueous polyester and the negative impact of insufficient content on the entanglement effect.

[0070] A stepwise stirring strategy was employed for mixing: First, the mixture was placed in a constant-temperature water bath at 55°C and mechanically stirred at a low speed of 60 rpm for 30 minutes. The technical considerations for choosing this temperature and stirring speed are that 55°C can increase the molecular motion rate of the system, promoting initial mixing, while avoiding the generation of bubbles caused by excessively high temperatures; the low stirring speed of 60 rpm can prevent the high-viscosity system from generating a large number of bubbles due to excessive stirring. If these bubbles cannot be removed, they will seriously affect the mechanical properties of the final product. The goal of this step is to form a millimeter-level premixed state, laying the foundation for subsequent molecular-level entanglement.

[0071] After premixing, the system is heated to 85°C and fine-mixed using magnetic stirring for 40 minutes until the system becomes a stable, opaque white mixture. Heating to 85°C aims to further increase the molecular chain movement rate, promoting the unentanglement and initial entanglement of polyvinyl alcohol and waterborne polyester molecular chains. Magnetic stirring is used instead of mechanical stirring because magnetic stirring has lower shear force, avoiding molecular chain breakage caused by mechanical stirring and ensuring the complete participation of molecular chains in entanglement. The 40-minute fine-mixing time ensures the entanglement reaction proceeds fully, forming a homogeneous mixture.

[0072] Finally, the entire system was placed in a high-pressure reactor at 120℃ and 103KPa for 25 minutes to obtain a bubble-free pre-crosslinked fluid. The high temperature and high pressure conditions eliminate residual microbubbles in the system and promote the full entanglement of molecular chains, forming a stable network structure. The 25-minute holding time ensures complete entanglement, and the pre-crosslinked fluid formed under these conditions exhibits good fluidity at 60-80℃, providing the necessary conditions for subsequent integrated molding.

[0073] Step 3: Integrated molding of artificial meniscus

[0074] The core of this step is to precisely mold the pre-crosslinked fluid into a product that matches the shape of the original meniscus, while avoiding defects during the molding process. The specific steps are as follows:

[0075] The pre-crosslinked fluid obtained in step two is placed in a constant temperature oven and heated to 75°C to form a well-flowing gel fluid. Simultaneously, a PTFE (polytetrafluoroethylene) meniscus mold is heated to 70°C in a forced-air drying oven, maintaining a temperature difference of 5°C between the gel fluid and the mold. PTFE was chosen as the mold material because of its excellent release properties, preventing the gel fluid from sticking to the mold and ensuring smooth removal of the product after molding. Maintaining a 5°C temperature difference is a key technical parameter in the molding process. Repeated verification has shown that this temperature difference balances the flowability of the gel fluid and the molding speed: an excessively large temperature difference will cause the gel fluid to cool and solidify rapidly during injection into the mold, failing to completely fill the mold cavity; an excessively small temperature difference will cause the gel fluid to flow too quickly, leaking from the mold's vents and compromising the product's shape integrity.

[0076] The gel fluid is poured into a dedicated feeding container and placed under the pressing head device. A pressure of 0.4 MPa is applied pneumatically to force the gel fluid into the preheated mold through the discharge port. Pressing is stopped when gel seeps out from the mold's venting port. The technical reason for controlling the pressing pressure to 0.4 MPa is that this pressure ensures that the gel fluid completely fills each cavity of the mold, replicating the anatomical shape of the meniscus and avoiding internal pores or morphological defects in the product due to insufficient pressure. Stopping pressing when gel seeps out from the venting port ensures that the mold is completely filled with gel fluid, while avoiding mold damage or product overflow caused by excessive pressure.

[0077] Allow the mold to cool naturally to room temperature, then open the mold and remove the preliminarily formed artificial meniscus. Natural cooling allows for the even release of internal stress, preventing cracking or deformation caused by rapid cooling and ensuring product shape stability.

[0078] Step 4: Artificial Meniscus Reinforcement

[0079] The core of this step is to lock in the molecular chain entanglement state through a closed-loop process of freeze-drying-hydration, thereby improving the product's structural stability and fatigue resistance. The specific operation is as follows:

[0080] The pre-formed artificial meniscus was placed in a -20°C freezer for 14 hours. The technical principle of low-temperature freezing is that low temperature can significantly reduce the molecular chain movement rate, promoting the formation of a more stable entangled structure between polyvinyl alcohol and water-based polyester molecular chains, and avoiding the depolymerization of entanglement caused by molecular thermal motion at room temperature; the 14-hour freezing time ensures that the product is completely frozen inside and the entangled structure is fully stable.

[0081] The frozen product was removed and placed in a vacuum drying oven. The vacuum level was set to -0.085 MPa and the temperature to 37°C for 19 hours of vacuum drying. The technical considerations for controlling this vacuum level and temperature are as follows: the high vacuum level of -0.085 MPa allows for rapid removal of free water from the product while preventing structural collapse due to excessive vacuum; the drying temperature of 37°C removes free water without affecting the bound water between molecular chains. If the temperature is too high, bound water will be lost, leading to damage to the entangled structure; if the temperature is too low, the drying time will be significantly prolonged, affecting production efficiency; the 19-hour drying time ensures complete removal of free water and a firmly locked entangled structure.

[0082] After vacuum drying, the product is immersed in deionized water for more than 12 hours to obtain an enhanced artificial meniscus. The purpose of the hydration treatment is to allow the product to reabsorb free water, restore the elasticity and biocompatibility of the hydrogel, and make its performance close to the water content of the original meniscus to meet clinical implantation requirements; the immersion time of more than 12 hours ensures that the product fully absorbs liquid and achieves a stable mechanical property state.

[0083] Example 2

[0084] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0085] Weigh 10g of polypropylene glycol (PPG, molecular weight 3000), 12g of polyethylene glycol (PEG, molecular weight 2000), 5g of isocyanate (IPDI), and 0.1g of stannous octoate, and place them in a three-necked flask. In this example, the mass ratio of PPG to PEG remains 1:1.2, maintaining the same proportional logic as in Example 1, ensuring a balance between the linear structure and hydrophilicity of the polyester. The amount of IPDI added is reduced to 5g, and the amount of stannous octoate added is reduced to 0.1g. The corresponding reaction conditions are adjusted to raise the temperature to 70°C, the stirring speed to 100r / min, and the reaction time to 3 hours. The technical consideration for this adjustment is that reducing the amount of IPDI will reduce the reaction rate. Therefore, by lowering the temperature, slowing down the stirring speed, and extending the reaction time, the polymerization reaction is ensured to proceed fully, avoiding excessively short molecular chains.

[0086] First, add 10 mL of acetone, stir well, then add 3 g of DMPA and react for 2 hours. Second, add 10 mL of acetone and 2 mL of TEA, and react at 40°C for 30 minutes. The amount of DMPA added is reduced to 3 g to match the amount of IPDI, ensuring the uniform introduction of hydrophilic groups; the amount of TEA added is reduced to 2 mL to match the carboxyl content of DMPA, achieving complete neutralization; the reaction temperature of 40°C is suitable for the neutralization reaction requirements after the reduction of TEA amount, avoiding excessive temperature that would cause TEA volatilization.

[0087] After the reaction was complete, deionized water was added at a rate of 5 mL / min using a peristaltic pump. During the process, 5 mL of acetone was added a third time, and the stirring speed was increased to 300 r / min. Finally, the acetone was removed by vacuum filtration, yielding a linear aqueous polyester with a number average molecular weight of 5000. The deionized water addition rate was reduced to 5 mL / min to accommodate the reaction termination requirements after a reduction in IPDI usage, ensuring that the molecular chain length was controlled within the 5000-20000 range specified in the claims. The stirring speed was reduced to 300 r / min to match the decrease in system viscosity, avoiding excessive stirring that could lead to molecular chain breakage.

[0088] Step 2: Preparation of fatigue-resistant hydrogel pre-crosslinked fluid

[0089] 30g of polyvinyl alcohol with a molecular weight of 70,000 was accurately weighed and dissolved in 50mL of deionized water at 120℃ and 103KPa. After cooling to room temperature, 5g of the aqueous polyester prepared in step one (mass ratio 1:6) was added. The amount of polyvinyl alcohol added was reduced to 30g, and the amount of aqueous polyester added was reduced to 5g, maintaining a mass ratio of 1:6. This ratio was experimentally verified to ensure sufficient molecular chain entanglement even with reduced raw material usage. Polyvinyl alcohol with a molecular weight of 70,000 was selected to form a suitable entanglement system with the low molecular weight aqueous polyester (5000) prepared in this example.

[0090] The premixing process was adjusted to 50℃ and 80 r / min for 30 minutes; the fine mixing temperature was increased to 80℃ and stirred for 40 minutes; finally, it was maintained at 120℃ and 103 kPa for 20 minutes to obtain the pre-crosslinked fluid. The premixing temperature was lowered to 50℃ and the stirring speed was increased to 80 r / min to accommodate the decrease in system viscosity after reducing the amount of raw materials, ensuring millimeter-level premixing effect; the fine mixing temperature was lowered to 80℃ and the holding time was shortened to 20 minutes to match the entanglement characteristics of low molecular weight polyester and avoid excessive entanglement that would lead to loss of system fluidity.

[0091] Step 3: Integrated molding of artificial meniscus

[0092] The pre-crosslinked fluid is heated to 70°C to form a gel fluid. The mold is preheated to 65°C (temperature difference of 5°C). The fluid is injected into the mold at a pressure of 0.3 MPa through a pressing device. Pressing is stopped when gel seeps out from the vent hole. After cooling to room temperature, the preliminary molded product is removed. The temperature of both the gel fluid and the mold is reduced to maintain a 5°C temperature difference to ensure the stability of the molding process. The pressing pressure is reduced to 0.3 MPa to match the reduced amount of gel fluid used, avoiding excessive pressure that could cause product overflow or mold damage.

[0093] Step 4: Artificial Meniscus Reinforcement

[0094] The pre-formed product was frozen at -20°C for 12 hours, then dried in a vacuum drying oven at -0.085MPa and 35°C for 18 hours, and finally immersed in deionized water for 12 hours to obtain the reinforced artificial meniscus. The freezing, drying, and hydration times were all appropriately shortened to match the reduced product usage, ensuring sufficient reinforcement while improving production efficiency.

[0095] Example 3

[0096] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0097] Weigh 10g of polypropylene glycol (PPG, molecular weight 2500), 15g of polyethylene glycol (PEG, molecular weight 1500), 12g of isocyanate (IPDI), and 0.3g of stannous octoate into a three-necked flask. In this embodiment, the mass ratio of PPG to PEG is 1:1.5, which is the upper limit of the scope defined in the claims. Experiments have verified that this ratio can further improve the hydrophilicity and linear structural integrity of the polyester, making the subsequent entanglement with polyvinyl alcohol more compact. The IPDI addition amount is the upper limit of 12g, and the stannous octoate addition amount is 0.3g. The corresponding reaction conditions are adjusted to heat to 80℃, stirring speed 200r / min, and reaction time shortened to 2 hours. The technical consideration for selecting these process parameters is that increasing the amount of IPDI will increase the reaction rate. Therefore, by increasing the temperature, accelerating the stirring speed, and shortening the reaction time, the polymerization reaction is ensured to be sufficient and uniform, avoiding local over-crosslinking, and finally obtaining a linear waterborne polyester with a number average molecular weight of 20,000. This molecular weight is at the upper limit of the scope defined in the claims and can form a more stable entangled network with high molecular weight polyvinyl alcohol.

[0098] First, add 15 mL of acetone, stir well, then add 5 g of DMPA and react for 1 hour. Second, add 15 mL of acetone and 4 mL of TEA, and react at 50°C for 30 minutes. The maximum amount of DMPA added is 5 g, which matches the high amount of IPDI to ensure the introduction of sufficient hydrophilic groups and improve the water solubility of the polyester. The amount of TEA added is 4 mL, which perfectly matches the carboxyl content of DMPA to achieve complete neutralization. The reaction temperature of 50°C can accelerate the neutralization reaction rate and meet the reaction requirements of high-volume raw materials.

[0099] After the reaction was complete, deionized water (the upper limit of the scope defined in the claims) was added at a rate of 10 mL / min using a peristaltic pump. During the process, 10 mL of acetone was added for the third time, and the stirring speed was increased to 500 rpm. Finally, the acetone was removed by vacuum filtration. Increasing the deionized water addition rate to 10 mL / min was to accommodate the rapid polymerization reaction caused by the high IPDI dosage and to precisely terminate the reaction to avoid excessively long molecular chains or cross-linking. Increasing the stirring speed to 500 rpm effectively dispersed the high-viscosity system, ensuring uniform dispersion of polyester molecules and laying the foundation for subsequent entanglement.

[0100] Step 2: Preparation of fatigue-resistant hydrogel pre-crosslinked fluid

[0101] Accurately weigh 50g of polyvinyl alcohol with a molecular weight of 80,000 (the upper limit of the scope defined in the claims), dissolve it in 100mL of deionized water at 120℃ and 103KPa, and after cooling to room temperature, add 10g of the aqueous polyester prepared in step one. At this point, the mass ratio of the aqueous polyester to the polyvinyl alcohol solution is 1:10 (the upper limit of the scope defined in the claims). The selection of polyvinyl alcohol with a molecular weight of 80,000 forms the optimal entanglement match with the high molecular weight aqueous polyester (20,000) prepared in this embodiment. The synergistic effect of the molecular chain length can significantly improve the entanglement density. The 1:10 mass ratio was determined through experimental optimization, ensuring that the aqueous polyester molecular chains are fully dispersed in the polyvinyl alcohol solution, avoiding uneven entanglement caused by local aggregation. Simultaneously, the high proportion of polyvinyl alcohol ensures the elasticity of the system.

[0102] A stepwise stirring strategy was employed for mixing: First, the mixture was placed in a constant-temperature water bath at 60°C and mechanically stirred at a low speed of 70 r / min for 30 minutes. Choosing a premixing temperature of 60°C (the upper limit of the scope defined in the claims) further enhances the molecular motion rate and promotes initial mixing; the stirring speed of 70 r / min avoids bubble formation while meeting the mixing requirements of high-viscosity systems. The goal of this step is to form a uniform, millimeter-scale premixed state, providing sufficient conditions for molecular-level entanglement.

[0103] After premixing, the system is heated to 90°C (the upper limit of the range defined in the claims), and then fine-mixed using magnetic stirring for 45 minutes (the upper limit of the range defined in the claims) until the system becomes a stable, opaque white mixture. Heating to 90°C maximizes the molecular chain movement rate, promoting the full unentanglement and initial entanglement of polyvinyl alcohol and aqueous polyester molecular chains; the 45-minute fine-mixing time ensures complete entanglement reaction, avoiding performance defects caused by insufficient mixing; and magnetic stirring avoids the shearing damage to high molecular weight molecular chains caused by mechanical stirring, ensuring that the molecular chains fully participate in entanglement.

[0104] Finally, the entire system was placed in a high-pressure reactor at 120℃ and 103KPa and maintained for 30 minutes (the upper limit of the scope defined in the claims) to obtain a pre-crosslinked fluid free of bubbles. Extending the high-temperature and high-pressure holding time to 30 minutes can further eliminate residual microbubbles in the system, while strengthening the degree of molecular chain entanglement, making the structure of the pre-crosslinked fluid more stable and less prone to defects during the molding process.

[0105] Step 3: Integrated molding of artificial meniscus

[0106] The pre-crosslinked fluid obtained in step two is placed in a constant temperature oven and heated to 80°C (the upper limit of the scope defined in the claims) to form a gel fluid with good flowability. Simultaneously, a polytetrafluoroethylene (PTFE) meniscus mold is heated to 70°C in a forced-air drying oven, controlling the temperature difference between the gel fluid and the mold to be 10°C (the upper limit of the scope defined in the claims). Choosing a gel fluid temperature of 80°C adapts to the flowability requirements of the high molecular weight entangled system, avoiding poor flow due to excessively low temperatures. The 10°C temperature difference, experimentally verified, ensures that the fluid fully fills the mold while preventing overflow caused by excessively fast flow, ensuring that the product shape accurately replicates the anatomical structure of the original meniscus.

[0107] The gel fluid is poured into a dedicated feeding container and placed under the pressing head device. A pressure of 0.5 MPa (the upper limit of the scope defined in the claims) is applied pneumatically to force the gel fluid into the preheated mold from the discharge port. Pressing is stopped when gel seeps out from the mold's venting port. Using a pressing pressure of 0.5 MPa ensures that the high molecular weight, high viscosity gel fluid completely fills each cavity of the mold, avoiding internal pores or morphological defects caused by insufficient pressure, and ensuring the structural integrity of the product.

[0108] Allow the mold to cool naturally to room temperature, then open the mold and remove the preliminarily formed artificial meniscus. Natural cooling allows for the even release of internal stress, preventing cracking or deformation of the high molecular weight system caused by rapid cooling and ensuring the stability of the product's shape.

[0109] Step 4: Artificial Meniscus Reinforcement

[0110] The pre-formed artificial meniscus was placed in a freezer at -20°C and frozen for 16 hours (the upper limit of the scope defined in the claims). Extending the freezing time to 16 hours ensures the complete stability of the entangled structure of the high molecular weight molecular chains, avoids the depolymerization of entanglement caused by molecular thermal motion at room temperature, and lays the foundation for subsequent drying and fixation.

[0111] The frozen product was removed and placed in a vacuum drying oven. The vacuum level was set to -0.09 MPa (the upper limit of the claims) and the temperature to 40°C (the upper limit of the claims), and vacuum drying was performed for 20 hours (the upper limit of the claims). The high vacuum level of -0.09 MPa quickly removes free water from the product while preventing the collapse of the high molecular weight structure due to excessive vacuum. The drying temperature of 40°C removes free water without affecting the bound water between molecular chains. The 20-hour drying time ensures complete removal of free water, firmly locking in the entangled structure and improving the product's mechanical stability.

[0112] After vacuum drying, the product is immersed in deionized water for 15 hours (the upper limit of the scope defined in the claims) to obtain an enhanced artificial meniscus. Extending the hydration time to 15 hours ensures that the high molecular weight system fully absorbs liquid, restores the elasticity and biocompatibility of the hydrogel, and stabilizes its properties.

[0113] Example 4 (Median Parameter Adaptation Example)

[0114] This embodiment uses the median process parameters and raw material ratios within the scope defined by the claims to verify the feasibility and stability of the scheme in conventional application scenarios, further illustrating the universality of the scheme. The specific operation is as follows:

[0115] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0116] Weigh 10g of polypropylene glycol (PPG, molecular weight 2000), 13g of polyethylene glycol (PEG, molecular weight 1000), 10g of isocyanate (IPDI), and 0.2g of stannous octoate, and place them in a three-necked flask. In this example, the mass ratio of PPG to PEG is 1:1.3, which is the median value within the scope defined in the claims. Experimental verification has shown that this ratio can balance the hydrophilicity and mechanical properties of polyester and is suitable for most clinical scenarios. The amount of IPDI added is 10g (median value), the amount of stannous octoate added is 0.2g (median value), and the corresponding reaction conditions are adjusted to a temperature of 72℃ (median value), a stirring speed of 120r / min (median value), and a reaction time of 2.8 hours (median value). The technical consideration for selecting this set of median process parameters is that it ensures a mild and complete polymerization reaction, avoiding performance fluctuations caused by parameters that are too high or too low, and ultimately obtaining a linear waterborne polyester with a number-average molecular weight of 11,000. This molecular weight is within the median range defined in the claims, has good versatility, and can form stable entanglements with polyvinyl alcohols of different molecular weights.

[0117] The first addition was 11 mL of acetone (median value), followed by thorough stirring and then 3.5 g of DMPA (median value). The reaction was allowed to proceed for 1.2 hours (median value). The second addition was 11 mL of acetone (median value) and 2.5 mL of TEA (median value), and the reaction was carried out at 42°C (median value) for 30 minutes. The median amounts of DMPA and TEA were used to match the median amount of IPDI, ensuring the introduction of appropriate amounts of hydrophilic groups. This improved the water solubility of the polyester while avoiding increased system brittleness due to excessive groups. The reaction temperature of 42°C balanced the reaction rate and stability, meeting the needs of routine production.

[0118] After the reaction was complete, deionized water (median value) was added at a rate of 6 mL / min using a peristaltic pump. During the process, 6 mL of acetone (median value) was added for the third time, and the stirring speed was increased to 350 r / min (median value). Finally, the acetone was removed by vacuum filtration. Using the median deionized water addition rate and stirring speed allows for precise control of reaction termination, ensuring uniform molecular chain length and providing a foundation for subsequent uniform entanglement.

[0119] Step 2: Preparation of fatigue-resistant hydrogel pre-crosslinked fluid

[0120] Accurately weigh 35g of polyvinyl alcohol (molecular weight 75000, median) and dissolve it in 60mL of deionized water at 120℃ and 103KPa. After cooling to room temperature, add 6g of the aqueous polyester prepared in step one. At this point, the mass ratio of the aqueous polyester to the polyvinyl alcohol solution is 1:7 (median). Selecting polyvinyl alcohol with a molecular weight of 75000 (median) and aqueous polyester with a median molecular weight (11000) forms a universal entanglement match, suitable for most clinical needs regarding mechanical properties and elasticity. The 1:7 mass ratio (median) was determined through experimental optimization, ensuring entanglement density while avoiding molding difficulties caused by excessively high system viscosity.

[0121] A stepwise mixing strategy is employed: first, the mixture is placed in a constant temperature water bath at 52℃ (median) and mechanically stirred at a low speed of 65 r / min (median) for 30 minutes. The median premixing temperature and stirring speed balance mixing efficiency and bubble control, adapting to the batch processing needs in conventional production, and forming a uniform millimeter-level premixed state.

[0122] After premixing, heat the system to 82°C (median) and use magnetic stirring for fine mixing for 35 minutes (median), until the system becomes a stable, opaque white mixture. The median fine mixing temperature and time ensure a complete and efficient entanglement reaction, avoiding energy waste due to excessively high parameters or insufficient mixing due to excessively low parameters.

[0123] Finally, the entire system was placed in a high-pressure reactor at 120℃ and 103KPa and maintained for 22 minutes (median value) to obtain a bubble-free pre-crosslinked fluid. The median high-temperature and high-pressure holding time can improve production efficiency while ensuring entanglement effect, making it suitable for industrial mass production.

[0124] Step 3: Integrated molding of artificial meniscus

[0125] The pre-crosslinked fluid obtained in step two is placed in a constant temperature oven and heated to 72°C (median value) to form a well-flowing gel fluid. Simultaneously, a polytetrafluoroethylene (PTFE) meniscus mold is heated to 65°C in a forced-air drying oven, maintaining a temperature difference of 7°C (median value) between the gel fluid and the mold. This median gel fluid temperature and temperature difference balances flowability and molding speed, making it suitable for batch molding with conventional molds and ensuring product consistency.

[0126] Pour the gel fluid into a dedicated feeding container and place it under the pressing head device. Apply a pressure of 0.35 MPa (median value) pneumatically to force the gel fluid into the preheated mold through the discharge port. Stop pressing when gel seeps out from the mold's venting port. The median pressing pressure ensures sufficient filling while avoiding mold damage caused by excessive pressure, thus reducing production costs.

[0127] The mold was allowed to cool naturally to room temperature. The mold was then opened to remove the pre-formed artificial meniscus, which was accurate in shape and without obvious defects, meeting the morphological adaptation requirements for clinical implantation.

[0128] Step 4: Artificial Meniscus Reinforcement

[0129] The pre-formed artificial meniscus was placed in a freezer at -20°C and frozen for 13 hours (median value). The median freezing time ensures the stability of the entangled structure while avoiding prolonged production cycles due to excessive freezing.

[0130] The frozen product is removed and placed in a vacuum drying oven. The vacuum level is set to -0.085 MPa (median) and the temperature to 36°C (median), and vacuum drying is carried out for 18.5 hours (median). The median vacuum level, drying temperature, and time can balance the drying effect and production efficiency, ensure that free water in the product is completely removed, and avoid structural damage caused by excessively high parameters.

[0131] After vacuum drying, the product is immersed in deionized water for 13 hours (median) to obtain an enhanced artificial meniscus.

[0132] Example 5

[0133] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0134] Weigh 10g of polypropylene glycol (PPG, molecular weight 3000), 14g of polyethylene glycol (PEG, molecular weight 2000), 7g of isocyanate (IPDI), and 0.15g of stannous octoate, and place them in a three-necked flask. In this example, the mass ratio of PPG to PEG is 1:1.4, which is in the high-mid range of the claims. Experiments have verified that this ratio can further improve the mechanical reinforcing properties of polyester while retaining good hydrophilicity, meeting the needs of preparing high-performance artificial menisci. The amount of IPDI added is 7g (high-mid value), and the amount of stannous octoate added is 0.15g (mid value). The corresponding reaction conditions are adjusted as follows: temperature raised to 78℃ (high-mid value), stirring speed 180r / min (high-mid value), and reaction time 2.2 hours (low-mid value). The technical consideration for selecting this set of parameters is that a higher reaction temperature and stirring speed can match a medium to high amount of IPDI, accelerate the reaction rate, and shorten the reaction time to avoid excessive cross-linking of molecular chains, ultimately obtaining a linear waterborne polyester with a number average molecular weight of 16,000. This molecular weight is in the medium to high range of the claims, and can form a denser entangled network with high molecular weight polyvinyl alcohol.

[0135] The first step involves adding 14 mL of acetone (medium-high value), stirring thoroughly, and then adding 4.5 g of DMPA (medium-high value), reacting for 1.8 hours (medium-high value). The second step involves adding 14 mL of acetone (medium-high value) and 3.5 mL of TEA (medium-high value), reacting at 48°C (medium-high value) for 30 minutes. The addition of both DMPA and TEA is at a medium-high value to match the medium-high dosage of IPDI, ensuring the introduction of sufficient hydrophilic groups to improve the water solubility of the polyester and subsequent entanglement effect. The reaction temperature of 48°C accelerates the neutralization reaction rate, adapting to the reaction requirements of medium-high dosage raw materials and ensuring a complete reaction.

[0136] After the reaction was complete, deionized water (medium-high value) was added at a rate of 9 mL / min using a peristaltic pump. During the process, 9 mL of acetone (medium-high value) was added a third time, and the stirring speed was increased to 450 r / min (medium-high value). Finally, the acetone was removed by vacuum filtration. Using a medium-high value for deionized water addition and stirring speed allows for precise termination of the polymerization reaction in the medium-high reactivity system, avoiding excessively long molecular chains or cross-linking, while ensuring uniform dispersion of polyester molecules, laying the foundation for subsequent high-density entanglement with polyvinyl alcohol.

[0137] Step 2: Preparation of fatigue-resistant hydrogel pre-crosslinked fluid

[0138] 45g of polyvinyl alcohol with a molecular weight of 80,000 (upper limit) was accurately weighed and dissolved in 90mL of deionized water at 120℃ and 103KPa. After cooling to room temperature, 9g of the aqueous polyester prepared in step one was added. At this point, the mass ratio of aqueous polyester to polyvinyl alcohol solution was 1:9 (medium-high value). The selection of polyvinyl alcohol with a molecular weight of 80,000 (upper limit) and aqueous polyester with a medium-high molecular weight (16,000) forms a high-performance entanglement match. The synergistic effect of molecular chain length can significantly improve entanglement density and mechanical properties. The 1:9 mass ratio was determined through experimental optimization, which can improve the mechanical enhancement effect of the system while ensuring sufficient dispersion of aqueous polyester molecular chains, thus meeting the high-performance clinical requirements.

[0139] A stepwise stirring strategy was employed for mixing: First, the mixture was placed in a constant temperature water bath at 58℃ (medium-high value) and mechanically stirred at a low speed of 75 r / min for 30 minutes (medium-high value). Choosing a premixing temperature of 58℃ (medium-high value) further enhances molecular motion and promotes initial mixing; the stirring speed of 75 r / min (medium-high value) avoids bubble formation while meeting the mixing requirements of medium-to-high viscosity systems, resulting in a uniform millimeter-level premixed state and providing sufficient conditions for high-density molecular entanglement.

[0140] After premixing, the system is heated to 88℃ (medium-high value), and then fine-mixed using magnetic stirring for 42 minutes (medium-high value) until the system becomes a stable, opaque white mixture. Heating to 88℃ (medium-high value) maximizes the molecular chain movement rate, promoting the full unentanglement and initial entanglement of polyvinyl alcohol and waterborne polyester molecular chains; the 42-minute fine-mixing time (medium-high value) ensures complete entanglement reaction, avoiding performance defects caused by insufficient mixing; magnetic stirring avoids the shearing damage to high molecular weight molecular chains caused by mechanical stirring, ensuring that the molecular chains participate completely in entanglement.

[0141] Finally, the entire system was placed in a high-pressure reactor at 120℃ and 103KPa and maintained for 28 minutes (medium-high value) to obtain a bubble-free pre-crosslinked fluid. Extending the high-temperature and high-pressure holding time to 28 minutes (medium-high value) can further eliminate residual microbubbles in the system, while strengthening the entanglement of molecular chains, making the structure of the pre-crosslinked fluid more stable and its mechanical properties superior.

[0142] Step 3: Integrated molding of artificial meniscus

[0143] The pre-crosslinked fluid obtained in step two was placed in a constant temperature oven and heated to 78°C (medium-high value) to form a well-flowing gel fluid. Simultaneously, a polytetrafluoroethylene (PTFE) meniscus mold was heated to 70°C in a forced-air drying oven, maintaining a temperature difference of 8°C (medium value) between the gel fluid and the mold. Choosing a gel fluid temperature of 78°C (medium-high value) accommodates the flowability requirements of medium-to-high density entanglement systems, avoiding poor flow due to excessively low temperatures. The 8°C temperature difference (medium value), as verified experimentally, ensures sufficient fluid filling of the mold while preventing overflow caused by excessive flow speed, ensuring accurate replication of the original meniscus's anatomical structure in the product form, and laying a solid structural foundation for subsequent reinforcement processing.

[0144] Pour the gel fluid into a dedicated feeding container and place it under the pressing head device. Apply a pressure of 0.45 MPa (medium-high value) pneumatically to force the gel fluid into the preheated mold through the discharge port. Stop pressing when gel seeps out from the mold's venting port. Using a pressing pressure of 0.45 MPa (medium-high value) ensures that the medium-to-high density, high-viscosity gel fluid completely fills each cavity of the mold, avoiding internal pores or morphological defects caused by insufficient pressure, and ensuring the structural integrity and uniform mechanical properties of the product.

[0145] Allow the mold to cool naturally to room temperature, then open the mold and remove the preliminarily formed artificial meniscus. Natural cooling allows for the even release of internal stress, preventing cracking or deformation of the medium-to-high density system caused by rapid cooling, and ensuring the stability of the product's shape.

[0146] Step 4: Artificial Meniscus Reinforcement

[0147] The preliminarily formed artificial meniscus was placed in a freezer at -20°C and frozen for 15 hours (medium-high value). Extending the freezing time to 15 hours (medium-high value) ensures the complete stability of the entanglement structure of medium- and high-density molecular chains, avoids the deagglomeration of entanglement caused by molecular thermal motion at room temperature, and lays a solid foundation for subsequent drying and fixation.

[0148] The frozen product was removed and placed in a vacuum drying oven. The vacuum level was set to -0.085 MPa (medium value) and the temperature to 39°C (medium-high value), and vacuum drying was carried out for 19.5 hours (medium-high value). Using a vacuum level of -0.085 MPa (medium value) ensures stable removal of free water from the product, preventing the collapse of the medium-to-high density structure caused by excessive vacuum. The drying temperature of 39°C (medium-high value) removes free water without affecting the bound water between molecular chains. The 19.5-hour drying time (medium-high value) ensures complete removal of free water and firmly locks in the entangled structure, further improving the product's mechanical stability and fatigue resistance.

[0149] After vacuum drying, the product is immersed in deionized water for 14 hours (medium-high value) to obtain an enhanced artificial meniscus. Extending the hydration time to 14 hours (medium-high value) ensures that the medium-high density system fully absorbs liquid, restores the elasticity and biocompatibility of the hydrogel, and enables it to reach a stable high-performance state.

[0150] Example 6

[0151] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0152] Weigh 10g of polypropylene glycol (PPG, molecular weight 2500), 13.5g of polyethylene glycol (PEG, molecular weight 1500), 9g of isocyanate (IPDI), and 0.25g of stannous octoate into a three-necked flask. In this example, the mass ratio of PPG to PEG is 1:1.35, which is within the optimal range of the claims. Experimental verification shows that this ratio perfectly balances the mechanical reinforcing properties and hydrophilicity of polyester, making it suitable for most conventional high-performance clinical scenarios. The IPDI addition amount is 9g (optimal), and the stannous octoate addition amount is 0.25g (medium-high value). The corresponding reaction conditions are adjusted as follows: temperature rise to 74℃ (optimal), stirring speed 160r / min (optimal), and reaction time 2.4 hours (median). The technical consideration for selecting this set of parameters is that the median-optimal reaction temperature and stirring speed can be matched with the median-optimal amount of IPDI, ensuring a mild and efficient reaction while avoiding excessive cross-linking of molecular chains, ultimately obtaining a linear waterborne polyester with a number-average molecular weight of 13,000. This molecular weight is within the median-optimal range defined in the claims, and it has both good entanglement effect and processing fluidity.

[0153] The first addition was 13 mL of acetone (slightly optimal), followed by thorough stirring and then 4 g of DMPA (slightly optimal). The reaction was carried out for 1.6 hours (slightly optimal). The second addition was 13 mL of acetone (slightly optimal) and 3 mL of TEA (slightly optimal), and the reaction was carried out at 44°C (slightly optimal) for 30 minutes. The DMPA and TEA additions were at the moderate values, precisely matched to the moderately optimal IPDI dosage, ensuring the introduction of appropriate hydrophilic groups to improve the water solubility of the polyester and subsequent entanglement. The reaction temperature of 44°C (slightly optimal) balanced the reaction rate and stability, meeting the needs of conventional high-performance production.

[0154] After the reaction was complete, deionized water (median value) was added at a rate of 8 mL / min using a peristaltic pump. During the process, 7 mL of acetone (medium-low value) was added for the third time, and the stirring speed was increased to 400 r / min (median value). Finally, the acetone was removed by vacuum filtration. Using the median deionized water addition rate and stirring speed can precisely terminate the polymerization reaction of the median-optimal reactive system, ensuring uniform molecular chain length and laying the foundation for stable entanglement with polyvinyl alcohol in the subsequent reaction.

[0155] Step 2: Preparation of fatigue-resistant hydrogel pre-crosslinked fluid

[0156] 42g of polyvinyl alcohol with a molecular weight of 75,000 (slightly better than median) was accurately weighed and dissolved in 80mL of deionized water at 120℃ and 103KPa. After cooling to room temperature, 8g of the aqueous polyester prepared in step one was added. At this point, the mass ratio of the aqueous polyester to the polyvinyl alcohol solution was 1:8.5 (slightly better than median). The polyvinyl alcohol with a molecular weight of 75,000 (slightly better than median) formed a balanced entanglement match with the aqueous polyester (13,000) with a molecular weight of slightly better than median, resulting in both good mechanical properties and processing fluidity. The mass ratio of 1:8.5 (slightly better than median) was determined through experimental optimization, which can ensure the entanglement density while avoiding molding difficulties caused by excessively high system viscosity, thus balancing product performance and production efficiency.

[0157] A stepwise mixing strategy is employed: first, the mixture is placed in a constant temperature water bath at 54℃ (slightly optimal), and then mechanically stirred at a low speed of 70 r / min for 30 minutes (median). The slightly optimal premixing temperature and the median stirring speed balance mixing efficiency and bubble control, meeting the batch processing requirements of conventional high-performance production, and forming a uniform millimeter-level premixed state.

[0158] After premixing, the system was heated to 84°C (slightly optimal), and then fine-mixed using magnetic stirring for 38 minutes (slightly optimal), until the system became a stable, opaque white mixture. The optimal fine-mixing temperature and time ensured a complete and efficient entanglement reaction, avoiding energy waste due to excessively high parameters or insufficient mixing due to excessively low parameters.

[0159] Finally, the entire system was placed in a high-pressure reactor at 120℃ and 103KPa and held for 26 minutes (slightly better than median) to obtain a bubble-free pre-crosslinked fluid. The slightly better than median high-temperature and high-pressure holding time can improve production efficiency while ensuring entanglement effect, and is suitable for the needs of industrial mass production.

[0160] Step 3: Integrated molding of artificial meniscus

[0161] The pre-crosslinked fluid obtained in step two is placed in a constant temperature oven and heated to 74°C (slightly above the median) to form a well-flowing gel fluid. Simultaneously, a polytetrafluoroethylene (PTFE) meniscus mold is heated to 67°C in a forced-air drying oven, maintaining a temperature difference of 7°C (median) between the gel fluid and the mold. This slightly above-median gel fluid temperature and median temperature difference balance flowability and molding speed, making it suitable for batch molding with conventional molds and ensuring product consistency and performance stability.

[0162] Pour the gel fluid into a dedicated feeding container and place it under the pressing head device. Apply a pressure of 0.4 MPa (median value) pneumatically to force the gel fluid into the preheated mold through the discharge port. Stop pressing when gel seeps out from the mold's venting port. The median pressing pressure ensures sufficient filling while avoiding mold damage caused by excessive pressure, reducing production costs, and ensuring the integrity of the product structure.

[0163] The mold was allowed to cool naturally to room temperature. The mold was then opened to remove the pre-formed artificial meniscus, which was accurate in shape and without obvious defects, meeting the morphological adaptation requirements for routine high-performance clinical implantation.

[0164] Step 4: Artificial Meniscus Reinforcement

[0165] The pre-formed artificial meniscus was placed in a -20°C freezer for 14.5 hours (slightly better than median). This slightly better freezing time ensures the stability of the entangled structure while avoiding prolonged production cycles caused by excessive freezing, thus balancing product performance and production efficiency.

[0166] The frozen product is removed and placed in a vacuum drying oven. The vacuum level is set to -0.085 MPa (median) and the temperature to 38°C (slightly better than median), and vacuum drying is carried out for 19 hours (median). The median vacuum level, the slightly better than median drying temperature, and the median drying time can balance the drying effect and production efficiency, ensure that free water in the product is completely removed, and avoid structural damage caused by excessively high parameters, further fixing the molecular chain entanglement.

[0167] After vacuum drying, the product was immersed in deionized water for 13.5 hours (better than median) to obtain an enhanced artificial meniscus.

[0168] Example 7

[0169] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0170] Weigh 10g of polypropylene glycol (PPG, molecular weight 2200), 12.5g of polyethylene glycol (PEG, molecular weight 1200), 6g of isocyanate (IPDI), and 0.12g of stannous octoate, and place them in a three-necked flask. In this example, the mass ratio of PPG to PEG is 1:1.25, which is in the lower-middle range of the scope defined in the claims. Experimental verification shows that this ratio can reduce raw material costs while ensuring the basic mechanical reinforcement properties of polyester, and is suitable for routine clinical needs. The amount of IPDI added is 6g (low-middle value), and the amount of stannous octoate added is 0.12g (low value). The corresponding reaction conditions are adjusted to a temperature of 71℃ (low-middle value), a stirring speed of 130r / min (low-middle value), and a reaction time of 2.7 hours (high-middle value). The technical consideration for choosing this set of parameters is that a system with lower reactivity needs to extend the reaction time to ensure sufficient polymerization and avoid excessively short molecular chains, ultimately obtaining a linear aqueous polyester with a number-average molecular weight of 8000. This molecular weight is in the lower-middle range of the claims, combining good entanglement effect with cost advantage.

[0171] The first step involves adding 11.5 mL of acetone (low to medium value), stirring thoroughly, and then adding 3.2 g of DMPA (low to medium value), reacting for 1.3 hours (low to medium value). The second step involves adding 11.5 mL of acetone (low to medium value) and 2.2 mL of TEA (low value), reacting at 41°C (low to medium value) for 30 minutes. The addition amounts of DMPA and TEA are both low to medium value, precisely matching the low to medium dosage of IPDI, ensuring the introduction of an appropriate amount of hydrophilic groups, satisfying water solubility requirements while avoiding raw material waste; the reaction temperature of 41°C balances and neutralizes the reaction rate and energy consumption, adapting to low-cost production needs.

[0172] After the reaction was complete, deionized water (medium-low value) was added at a rate of 5.5 mL / min using a peristaltic pump. During the process, 5.5 mL of acetone (low value) was added a third time, and the stirring speed was increased to 320 r / min (medium-low value). Finally, the acetone was removed by vacuum filtration. Using a medium-low deionized water addition rate and stirring speed allows for precise termination of the polymerization reaction in a medium-low reactivity system, ensuring uniform molecular chain length while reducing stirring energy consumption, thus laying the foundation for stable entanglement with polyvinyl alcohol in the subsequent reaction.

[0173] Step 2: Preparation of fatigue-resistant hydrogel pre-crosslinked fluid

[0174] 33g of polyvinyl alcohol (PVA) with a molecular weight of 75,000 (low to medium molecular weight) was accurately weighed and dissolved in 55mL of deionized water at 120℃ and 103KPa. After cooling to room temperature, 5.5g of the aqueous polyester prepared in step one was added, resulting in a mass ratio of 1:6.5 (low to medium molecular weight) of the aqueous polyester to the PVA solution. The selection of PVA with a molecular weight of 75,000 (low to medium molecular weight) to form a suitable entanglement with the low to medium molecular weight aqueous polyester (8,000) reduces raw material costs while ensuring basic mechanical properties. The 1:6.5 mass ratio was determined through experimental optimization, which reduces the amount of PVA used while maintaining entanglement density, further controlling costs and making it suitable for routine clinical scenarios.

[0175] A stepwise stirring strategy was adopted for mixing: First, the mixture was placed in a constant temperature water bath at 51℃ (low to medium value) and mechanically stirred at a low speed of 62 r / min for 30 minutes (low to medium value). The low to medium premixing temperature and stirring speed can reduce energy consumption while avoiding bubble generation, meet the needs of low-cost mass production, form a uniform millimeter-level premixed state, and provide sufficient conditions for molecular-level entanglement.

[0176] After premixing, the system is heated to 81℃ (low to medium temperature) and fine-mixed using magnetic stirring for 32 minutes (low to medium temperature) until the system becomes a stable, opaque white mixture. Heating to 81℃ meets the basic requirements for molecular chain de-entanglement and re-entanglement, avoiding energy waste caused by excessively high temperatures; the 32-minute fine-mixing time ensures sufficient entanglement reaction and improves production efficiency; magnetic stirring avoids the shearing damage to molecular chains caused by mechanical stirring, ensuring that the molecular chains participate completely in entanglement.

[0177] Finally, the entire system was placed in a high-pressure reactor at 120℃ and 103KPa and held for 21 minutes (medium-low value) to obtain a bubble-free pre-crosslinked fluid. The medium-low value of high temperature and high pressure holding time can shorten the production cycle and reduce energy consumption costs while ensuring the entanglement effect, making it suitable for industrial mass production.

[0178] Step 3: Integrated molding of artificial meniscus

[0179] The pre-crosslinked fluid obtained in step two is placed in a constant temperature oven and heated to 71°C (low to medium temperature) to form a well-flowing gel fluid. Simultaneously, a polytetrafluoroethylene (PTFE) meniscus mold is heated to 63°C in a forced-air drying oven, maintaining a temperature difference of 8°C (medium temperature) between the gel fluid and the mold. This low to medium temperature reduces heating energy consumption, while the 8°C temperature difference, as experimentally verified, ensures the fluid fully fills the mold while preventing overflow due to excessive flow speed, thus ensuring the product accurately replicates the anatomical structure of the original meniscus.

[0180] Pour the gel fluid into a dedicated feeding container and place it under the pressing head device. Apply a pressure of 0.32 MPa (low to medium) pneumatically to force the gel fluid into the preheated mold through the discharge port. Stop pressing when gel seeps out from the mold's venting port. Using a pressing pressure of 0.32 MPa ensures that the low to medium viscosity gel fluid fully fills the mold while reducing equipment energy consumption and mold wear, further controlling production costs.

[0181] Allow the mold to cool naturally to room temperature, then open the mold and remove the preliminarily formed artificial meniscus. Natural cooling allows for the even release of internal stress, preventing cracking or deformation caused by rapid cooling and ensuring product shape stability.

[0182] Step 4: Artificial Meniscus Reinforcement

[0183] The pre-formed artificial meniscus was placed in a -20°C freezer for 12.5 hours (low to medium value). This low to medium freezing time ensures the stability of the entangled structure while shortening the production cycle, reducing freezing energy consumption, and balancing product performance with production costs.

[0184] The frozen product was removed and placed in a vacuum drying oven. The vacuum level was set to -0.085 MPa (medium value) and the temperature to 35.5℃ (low-medium value), and vacuum drying was carried out for 18.2 hours (low-medium value). The medium vacuum level can steadily remove free water from the product, while the low-medium drying temperature and time can reduce energy consumption, while ensuring that free water is completely removed from the product and the entangled structure is firmly locked.

[0185] After vacuum drying, the product is immersed in deionized water for 12.5 hours (medium to low value) to obtain an enhanced artificial meniscus.

[0186] Example 8

[0187] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0188] Weigh 10g of polypropylene glycol (PPG, molecular weight 2800), 14.5g of polyethylene glycol (PEG, molecular weight 1800), 11g of isocyanate (IPDI), and 0.28g of stannous octoate into a three-necked flask. In this example, the mass ratio of PPG to PEG is 1:1.45, which is within the upper-middle range of the scope defined in the claims. Experiments have verified that this ratio can maximize the mechanical reinforcing properties of the polyester while retaining excellent hydrophilicity, meeting the needs of high-performance clinical applications. The amount of IPDI added is 11g (upper-middle range), and the amount of stannous octoate added is 0.28g (upper-middle range). The corresponding reaction conditions are adjusted as follows: temperature increased to 79℃ (upper-middle range), stirring speed 190r / min (upper-middle range), and reaction time 2.1 hours (lower-middle range). The technical consideration for selecting this set of parameters is that the highly reactive system can increase the reaction rate through higher temperature and stirring speed, while shortening the reaction time to avoid excessive cross-linking of molecular chains, ultimately obtaining a linear waterborne polyester with a number average molecular weight of 18,000. This molecular weight is in the upper-middle range of the scope defined in the claims, and can form an ultra-dense entangled network with high molecular weight polyvinyl alcohol.

[0189] The first addition was 14.5 mL of acetone (slightly above the upper limit), followed by thorough stirring. Then, 4.8 g of DMPA (slightly above the upper limit) was added, and the reaction was allowed to proceed for 1.9 hours (medium-high value). The second addition was 14.5 mL of acetone (slightly above the upper limit) and 3.8 mL of TEA (slightly above the upper limit), and the reaction was carried out at 49°C (slightly above the upper limit) for 30 minutes. The addition amounts of DMPA and TEA were both set at the medium-high upper limit to match the high dosage of IPDI, ensuring the introduction of sufficient hydrophilic groups to improve the water solubility of the polyester and the subsequent ultra-dense entanglement effect. The reaction temperature of 49°C accelerated the neutralization reaction rate, meeting the reaction requirements of high-dosage raw materials and ensuring a complete reaction.

[0190] After the reaction was complete, deionized water (slightly above the upper limit) was added at a rate of 9.5 mL / min using a peristaltic pump. During the process, 9.5 mL of acetone (slightly above the upper limit) was added a third time, and the stirring speed was increased to 480 r / min (slightly above the upper limit). Finally, the acetone was removed by vacuum filtration. Using a deionized water addition rate slightly above the upper limit and a stirring speed that precisely terminates the polymerization reaction of the highly reactive system, avoiding excessively long molecular chains or cross-linking, while ensuring uniform dispersion of polyester molecules, laying the foundation for the subsequent ultra-dense entanglement with polyvinyl alcohol.

[0191] Step 2: Preparation of fatigue-resistant hydrogel pre-crosslinked fluid

[0192] 48g of polyvinyl alcohol with a molecular weight of 78,000 (mid-to-high upper limit) was accurately weighed and dissolved in 95mL of deionized water at 120℃ and 103KPa. After cooling to room temperature, 9.5g of the aqueous polyester prepared in step one was added, resulting in a mass ratio of 1:9.5 (mid-to-high upper limit) between the aqueous polyester and the polyvinyl alcohol solution. The selection of polyvinyl alcohol with a molecular weight of 78,000 (mid-to-high upper limit) and the aqueous polyester with a molecular weight of 18,000 (mid-to-high upper limit) forms a high-performance entanglement match. The synergistic effect of the molecular chain length significantly improves the entanglement density and mechanical properties. The 1:9.5 mass ratio was determined through experimental optimization, which maximizes the mechanical enhancement effect of the system while ensuring sufficient dispersion of the aqueous polyester molecular chains, thus meeting the high-performance clinical requirements.

[0193] A stepwise stirring strategy was employed for mixing: First, the mixture was placed in a constant temperature water bath at 59℃ (slightly above the upper limit) and mechanically stirred at a low speed of 78 r / min for 30 minutes (slightly above the upper limit). Choosing a premixing temperature of 59℃ (slightly above the upper limit) maximizes molecular motion rates and promotes initial mixing; the stirring speed of 78 r / min avoids bubble formation while meeting the mixing requirements of ultra-high viscosity systems, resulting in a uniform millimeter-level premixed state, providing sufficient conditions for molecular-level ultra-dense entanglement.

[0194] After premixing, the system was heated to 89°C (higher-middle limit), and then fine-mixed using magnetic stirring for 44 minutes (higher-middle limit), until the system became a stable, opaque white mixture. Heating to 89°C maximizes the molecular chain motion rate, promoting the full unentanglement and initial entanglement of polyvinyl alcohol and waterborne polyester molecular chains; the 44-minute fine-mixing time ensures complete entanglement reaction, avoiding performance defects caused by insufficient mixing; and magnetic stirring avoids the shearing damage to high molecular weight molecular chains caused by mechanical stirring, ensuring that the molecular chains fully participate in entanglement.

[0195] Finally, the entire system was placed in a high-pressure reactor at 120℃ and 103KPa and maintained for 29 minutes (slightly above the upper limit of the medium-high pressure) to obtain a pre-crosslinked fluid free of bubbles. Extending the high-temperature and high-pressure holding time to 29 minutes (slightly above the upper limit of the medium-high pressure) can further eliminate residual microbubbles in the system, while strengthening the degree of molecular chain entanglement, making the structure of the pre-crosslinked fluid more stable and its mechanical properties superior.

[0196] Step 3: Integrated molding of artificial meniscus

[0197] The pre-crosslinked fluid obtained in step two was placed in a constant temperature oven and heated to 79°C (higher-middle range) to form a well-flowing gel fluid. Simultaneously, a polytetrafluoroethylene (PTFE) meniscus mold was heated to 71°C in a forced-air drying oven, maintaining a temperature difference of 8°C (median) between the gel fluid and the mold. Choosing a gel fluid temperature of 79°C (higher-middle range) accommodates the flowability requirements of the ultra-dense entangled system, avoiding poor flow due to excessively low temperatures. The 8°C temperature difference, experimentally verified, ensures sufficient fluid filling of the mold while preventing overflow caused by excessive flow speed, ensuring the product accurately replicates the anatomical structure of the original meniscus and laying a solid structural foundation for subsequent reinforcement processing.

[0198] Pour the gel fluid into a dedicated feeding container and place it under the pressing head device. Apply a pressure of 0.48 MPa (slightly above the upper limit) pneumatically to force the gel fluid into the preheated mold through the discharge port. Stop pressing when gel seeps out from the mold's venting port. Using a pressing pressure of 0.48 MPa (slightly above the upper limit) ensures that the ultra-high density, high viscosity gel fluid completely fills every cavity of the mold, avoiding internal pores or morphological defects caused by insufficient pressure, and guaranteeing the structural integrity and uniform mechanical properties of the product.

[0199] Allow the mold to cool naturally to room temperature, then open the mold and remove the preliminarily formed artificial meniscus. Natural cooling allows for the even release of internal stress, preventing cracking or deformation of the ultra-high-density system caused by rapid cooling and ensuring the stability of the product's shape.

[0200] Step 4: Artificial Meniscus Reinforcement

[0201] The preliminarily formed artificial meniscus was placed in a freezer at -20°C and frozen for 15.5 hours (slightly above the upper limit of the medium-high temperature range). Extending the freezing time to 15.5 hours (slightly above the upper limit of the medium-high temperature range) ensures the complete stability of the entangled structure of the ultra-high density molecular chains, avoids the deagglomeration of entanglement caused by molecular thermal motion at room temperature, and lays a solid foundation for subsequent drying and fixation.

[0202] The frozen product was removed and placed in a vacuum drying oven. The vacuum level was set to -0.085 MPa (median) and the temperature to 39.5℃ (slightly above the upper limit), and vacuum drying was carried out for 19.8 hours (slightly above the upper limit). Using a vacuum level of -0.085 MPa (median) ensures stable removal of free water from the product, preventing the collapse of the ultra-high density structure caused by excessively high vacuum. The drying temperature of 39.5℃ (slightly above the upper limit) removes free water without affecting the bound water between molecular chains. The drying time of 19.8 hours (slightly above the upper limit) ensures complete removal of free water and firmly locks in the entangled structure, further improving the product's mechanical stability and fatigue resistance.

[0203] After vacuum drying, the product is immersed in deionized water for 14.5 hours (high to upper limit) to obtain an enhanced artificial meniscus.

[0204] See Figures 2-6 ,exist Figure 2 In the settings, WD=11.4mm indicates that the working distance of the scanning electron microscope (SEM) is 11.4 mm. The working distance refers to the perpendicular distance between the lens and the sample surface. This parameter determines the imaging resolution and depth of field. The optimized 11.4mm working distance clearly captures the microstructure of the gel while ensuring a complete image field of view, accurately presenting the overall morphology of the bimolecular entanglement. Mag=10.00KX indicates that the image magnification is 10000x (KX stands for "thousandth"). This magnification allows for precise focusing on the micro-network structure of the gel, clearly displaying the entanglement details of the aqueous polyester and polyvinyl alcohol molecular chains, avoiding structural blurring due to insufficient magnification or limited field of view due to over-magnification. FIBLockMags=No indicates that the focused ion beam (FIB) magnification locking function is not enabled. This test only requires observing the microstructure of the gel in its natural state, without the need for sample processing or precise positioning and magnification via FIB. This setting meets the testing requirements for pure structural observation, ensuring that the image reflects the true state of the sample. ZEISS: This refers to the brand of the scanning electron microscope (SEM), Zeiss. This brand's equipment possesses high-resolution imaging capabilities, and its test results are authoritative and reliable, corroborating the credibility of the microstructure characterization data in this invention. 2µm: This represents the scale bar in the lower right corner of the image, indicating that the corresponding length in the image represents 2 micrometers in the actual sample. This scale bar quantifies the pore size and molecular chain intertwining density of the gel entanglement network. Combined with the magnification, the average spacing of the entangled nodes can be calculated to be approximately several hundred nanometers, proving the formation of a dense and uniform bimolecular entanglement network. EHT=5.00kV: This indicates that the electron gun accelerating voltage (Extra High Tension) is 5.00 kilovolts. This accelerating voltage is adapted to the conductivity characteristics of the gel sample, ensuring both a moderate electron beam penetration depth for clear visualization of the internal structure and avoiding sample surface damage or charge accumulation caused by high voltage, thus ensuring image quality. SignalA=InLens: This indicates that the imaging signal is the secondary electron signal collected by the in-lens detector. The in-microscope detection mode features high spatial resolution, accurately capturing the morphological details of the sample surface, clearly distinguishing molecular chain entanglement nodes from the gel matrix, and intuitively presenting the intertwined state of bimolecular entanglement. Date: 2Apr2021: This indicates that the scanning electron microscope test was conducted on April 2, 2021, providing time traceability for the test data and ensuring the traceability and authenticity of the experimental results.

[0205] Figure 3In the graph, the horizontal axis represents retention time (Unit: min), which is the time it takes for the sample to be detected by the detector after separation in the chromatographic column. Different retention times correspond to polyester molecules of different molecular weights, and retention time is positively correlated with molecular weight (the larger the molecular weight, the longer the retention time). The vertical axis represents signal intensity (unitless, based on the values ​​marked on the chromatogram), reflecting the concentration of polyester molecules at the corresponding retention time. The higher the peak signal intensity, the higher the content of polyester molecules in that molecular weight range, used to characterize the uniformity of polyester molecular weight distribution.

[0206] Figure 4 In the graph, the horizontal axis represents retention time (Unit: min), used to distinguish the separation time of different residual solvents (triethylamine, acetone). Different solvents have different retention times in the chromatographic column due to differences in their physicochemical properties; retention time can be used to qualitatively identify the types of residual solvents. The vertical axis represents signal intensity (unitless, based on the values ​​labeled on the chromatogram), which is positively correlated with the concentration of residual solvents. The specific content of residual solvents is calculated through the peak area, used to verify whether the organic solvent residues in the product meet the requirements.

[0207] Figure 5 In the graph, the horizontal axis has no explicit numerical label and is used to classify test states, distinguishing only between "before fatigue" and "after fatigue" test conditions. This is used to compare the performance differences of the same artificial meniscus before and after cyclic fatigue testing. The vertical axis represents the compressive modulus (unit: MPa), reflecting the artificial meniscus's resistance to deformation under compressive load. A higher value indicates stronger compressive stability. The fatigue resistance of the product is characterized by the change in the value before and after fatigue (attenuation rate).

[0208] Figure 6 In the middle, the horizontal axis represents the number of friction cycles (unit: ×10). 6 (times), which refers to the number of friction reciprocations of the artificial meniscus under simulated joint movement conditions, ranging from 0 to 12 × 10⁻⁶. 6 Next, we simulated long-term use scenarios for the product. The vertical axis represents the coefficient of friction (COF, unitless), reflecting the magnitude of frictional resistance between the artificial meniscus and the contact interface. The lower the coefficient of friction and the more gradual its change with the number of cycles, the better the friction resistance and the better the lubrication effect can be maintained over a long period of time.

[0209] The following is a combination of the above. Figures 2-6 To provide comparative examples 1-8:

[0210] Comparative Example 1

[0211] Step 1: Raw material preparation

[0212] Weigh 50g of polycarbonate polyurethane granules (molecular weight 30,000) and dry them in a 100℃ drying oven for 4 hours to remove moisture and prevent air bubbles from forming during molding. This material is the mainstream choice for existing artificial menisci, and its high strength properties meet traditional load-bearing requirements.

[0213] Step 2: Injection Molding

[0214] The dried polycarbonate polyurethane granules are added to the injection molding machine barrel, which is set to 180℃. The mixture is held at this temperature for 30 minutes until completely melted. Simultaneously, the PTFE meniscus mold is preheated to 80℃. The molten fluid is then injected into the mold at a pressure of 1.0 MPa using the injection molding machine. After holding the pressure for 20 minutes, the mold is allowed to cool naturally to room temperature. The mold is then opened, and the partially formed product is removed. Conventional injection molding processes rely on high-temperature melting and high-pressure holding, representing the standard procedure for molding single polymer materials.

[0215] Step 3: Post-processing

[0216] The pre-formed product is ground and polished to remove surface burrs and flash, resulting in the finished artificial meniscus. Defects are prone to occur on the surface after single-material melting and molding; therefore, grinding and polishing are indispensable corrective steps in existing processes.

[0217] The artificial meniscus prepared in this comparative model had an elastic modulus of 1.5 MPa, a tensile strength of 5.0 MPa, and an elongation at break of 200%. After 10... 6 After several cycles of fatigue testing, the compressive modulus decreased by 25%, and the coefficient of friction was 0.22; its microstructure had no entangled network, but was only a dense homogeneous structure (with...). Figure 2 Significant differences are visible in the comparison; a comparison of compressive stability before and after fatigue shows a dramatic decrease (compared to...). Figure 5 (Comparison); the coefficient of friction increases continuously with the number of cycles (compared to) Figure 6 (In comparison), it has poor abrasion resistance and cannot balance strength and elasticity, and long-term use can easily damage cartilage.

[0218] Comparative Example 2

[0219] The same raw materials (waterborne polyester and polyvinyl alcohol) as in Example 1 of this invention are used, but the step-by-step mixing process is abandoned, and a traditional one-time mechanical stirring and mixing is adopted. The specific operation is as follows:

[0220] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0221] The linear waterborne polyester with a number average molecular weight of 12000 was prepared in complete consistency with step one of Example 1 of the present invention.

[0222] Step 2: One-time blending of two materials

[0223] 40g of polyvinyl alcohol with a molecular weight of 75,000 was accurately weighed and dissolved in 75mL of deionized water at 120℃ and 103KPa. After cooling to room temperature, 7g of the aqueous polyester prepared in step one was directly added. The mixture was placed at 85℃ and mechanically stirred at 300r / min for 60 minutes, followed by holding at 120℃ and 103KPa for 25 minutes to obtain the blended fluid. This step did not employ a stepwise mixing strategy, but directly achieved mixing through high-temperature mechanical stirring, which is a conventional process for existing two-material blending, but it is prone to generating bubbles and phase separation.

[0224] Step 3: Integrated Molding and Reinforcement Treatment

[0225] The process is completely consistent with steps three and four of Embodiment 1 of the present invention, namely, heating the gel fluid to 75°C, preheating the mold to 70°C (temperature difference of 5°C), injecting it into the mold under a pressure of 0.4MPa, freezing at -20°C for 14 hours, vacuum drying at 37°C and -0.085MPa for 19 hours, and soaking in deionized water for 12 hours.

[0226] The artificial meniscus prepared in this comparative example had an elastic modulus of 0.8 MPa, a tensile strength of 3.0 MPa, and an elongation at break of 280%. After 10... 6 After several cycles of fatigue testing, the compressive modulus decreased by 18%, and the coefficient of friction was 0.18; its microstructure showed obvious phase separation and bubbles (with) Figure 2 In comparison, the bimolecular chain entanglement was insufficient; residual solvent testing showed that the acetone residue was 0.05% (compared to...). Figure 4 In comparison, it is 0.01% higher than that of Example 1 of the present invention; the degree of decrease in compressive stability before and after fatigue is significantly higher than that of Example 1 (compared to Example 1). Figure 5 (Comparison) demonstrates that the stepwise mixing process is key to achieving full entanglement.

[0227] Comparative Example 3

[0228] The same raw materials and stepwise mixing process as in Example 2 of this invention are used, but the freeze-drying-hydration enhancement step is omitted. The specific operation is as follows:

[0229] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0230] The linear waterborne polyester with a number average molecular weight of 5000 was prepared in complete consistency with step one of Example 2 of the present invention.

[0231] Step 2: Preparation of fatigue-resistant hydrogel pre-crosslinked fluid

[0232] The process is completely consistent with step two of Example 2 of this invention, namely, 30g of polyvinyl alcohol is dissolved in 50mL of deionized water, 5g of waterborne polyester is added, and the mixture is premixed at low speed at 50℃, magnetically mixed at 80℃, and kept warm at high temperature and high pressure to obtain a pre-crosslinked fluid.

[0233] Step 3: Integrated Molding

[0234] The process is completely consistent with step three of Embodiment 2 of the present invention. The gel fluid is heated to 70°C, the mold is preheated to 65°C, and injected into the mold at a pressure of 0.3MPa. After cooling to room temperature, the finished product is obtained directly without freezing, drying, or hydration treatment.

[0235] The artificial meniscus prepared in this comparative example had an elastic modulus of 0.7 MPa, a tensile strength of 2.8 MPa, and an elongation at break of 300%. After 10... 6 After several cycles of fatigue testing, the compressive modulus decreased by 30%, and the coefficient of friction was 0.19; its microstructure showed loose molecular chain entanglement (and...). Figure 2 (In comparison), no dense entangled network was found; the molecular weight test curve showed a low degree of entanglement (compared to...). Figure 3 (Comparison) demonstrates that the freeze-dry-hydration process is crucial for locking entangled structures and improving stability.

[0236] Comparative Example 4

[0237] Using the same raw material ratio and process as in Example 3 of this invention, only the addition rate of deionized water in step one is changed. The specific operation is as follows:

[0238] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0239] Weigh 10g PPG (molecular weight 2500), 15g PEG (molecular weight 1500), 12g IPDI and 0.3g stannous octoate, heat to 80℃ and stir at 150r / min for 2 hours; the subsequent addition of acetone, DMPA and TEA is the same as in Example 3; after the reaction is completed, deionized water is added at a rate of 15mL / min using a peristaltic pump (50% higher than the upper limit of the scope of the claims), and 10mL acetone is added for the third time, stirred at 400r / min, and vacuum filtered to remove acetone, to obtain a cross-linked waterborne polyester with a number average molecular weight of 28000 (the molecular chains are too long and partially cross-linked).

[0240] Steps two through four

[0241] The process is completely consistent with steps two to four of Embodiment 3 of the present invention, namely, 50g of polyvinyl alcohol and 10g of waterborne polyester are mixed, and a pre-crosslinked fluid is prepared by stepwise stirring. The fluid is then molded at 70°C and 80°C (temperature difference of 10°C), frozen for 16 hours, vacuum dried for 20 hours, and hydrated for 15 hours.

[0242] The artificial meniscus prepared in this comparative example had an elastic modulus of 1.3 MPa, a tensile strength of 3.8 MPa, and an elongation at break of 250% after 10... 6After several cycles of fatigue testing, the compressive modulus decreased by 15%, and the coefficient of friction was 0.17; its microstructure showed partially cross-linked aggregates (and... Figure 2 In comparison), the molecular weight distribution is uneven (compared to...). Figure 3 (Comparison) demonstrates that uncontrolled addition of deionized water leads to abnormal molecular chain structure, affecting entanglement effect and performance balance.

[0243] Comparative Example 5

[0244] Using the same raw material ratio and process as in Example 4 of this invention, only the premixing temperature in step two is changed. The specific operation is as follows:

[0245] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0246] The linear waterborne polyester with a number average molecular weight of 11,000 was prepared in complete consistency with step one of Example 4 of the present invention.

[0247] Step 2: Preparation of fatigue-resistant hydrogel pre-crosslinked fluid

[0248] 35g of polyvinyl alcohol was accurately weighed and dissolved in 60mL of deionized water, and 6g of waterborne polyester was added. The mixture was placed in a constant temperature water bath at 70°C (10°C above the limit of the claims) and mechanically stirred at a low speed of 65r / min for 30 minutes. The subsequent fine mixing at 82°C and high temperature and high pressure heat preservation were the same as in Example 4, resulting in a pre-crosslinked fluid containing a large number of bubbles.

[0249] Steps 3 to 4

[0250] The process is completely consistent with steps three to four of Embodiment 4 of the present invention, namely, the gel fluid at 72°C is molded with a mold at 65°C (temperature difference of 7°C), frozen for 13 hours, vacuum dried for 18.5 hours, and hydrated for 13 hours.

[0251] The artificial meniscus prepared in this comparative example had an elastic modulus of 0.9 MPa, a tensile strength of 3.9 MPa, and an elongation at break of 330% after 10... 6 After several cycles of fatigue testing, the compression modulus decreased by 12%, and the coefficient of friction was 0.16; its internal bubble content was relatively high (compared to...). Figure 2 (In comparison), residual solvent testing showed a slightly higher acetone residue (compared to...). Figure 4 (Comparison) demonstrates that exceeding the premixing temperature standard will lead to the formation of bubbles, affecting the product's density and performance.

[0252] Comparative Example 6 (Molding Temperature Difference Runaway Solution)

[0253] Using the same raw material ratio and process as in Example 5 of this invention, only the temperature difference between the gel fluid and the mold in step three is changed. The specific operation is as follows:

[0254] Steps 1 to 2

[0255] The pre-crosslinked fluid is prepared in complete consistency with steps one to two of Example 5 of the present invention.

[0256] Step 3: Integrated Molding

[0257] The pre-crosslinked fluid is heated to 78°C, and the mold is preheated to 58°C, so that the temperature difference is controlled at 20°C (100% above the upper limit of the scope defined in the claims). The fluid is injected into the mold under a pressure of 0.45 MPa. When gel seeps out from the vent hole, the pressing is stopped. After cooling to room temperature, the preliminary molded product is taken out.

[0258] Step 4: Artificial Meniscus Reinforcement

[0259] This is completely consistent with step four of embodiment 5 of the present invention, namely freezing for 15 hours, vacuum drying for 19.5 hours, and hydration for 14 hours.

[0260] The artificial meniscus prepared in this comparative example had an elastic modulus of 0.85 MPa, a tensile strength of 3.7 MPa, and an elongation at break of 320% after 10... 6 After several cycles of fatigue testing, the compression modulus decreased by 14%, and the coefficient of friction was 0.17; the product edges showed incomplete filling defects, and the internal stress distribution was uneven (compared to...). Figure 2 In comparison), fatigue stability is slightly worse (compared to...). Figure 5 (Comparison) demonstrates that uncontrolled molding temperature difference can disrupt the balance between fluidity and molding integrity.

[0261] Comparative Example 7

[0262] Using the same raw materials and process as in Example 6 of this invention, only the mass ratio of waterborne polyester to polyvinyl alcohol is changed. The specific operation is as follows:

[0263] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0264] The linear waterborne polyester with a number-average molecular weight of 13,000 was prepared in complete consistency with step one of Example 6 of the present invention.

[0265] Step 2: Preparation of fatigue-resistant hydrogel pre-crosslinked fluid

[0266] 42g of polyvinyl alcohol was accurately weighed and dissolved in 80mL of deionized water, and 12g of aqueous polyester was added to make the mass ratio 1:5.5 (lower than the lower limit of the scope defined in the claims); the subsequent premixing at 54°C, fine mixing at 84°C and high temperature and high pressure heat preservation were the same as in Example 6 to obtain a pre-crosslinked fluid.

[0267] Steps 3 to 4

[0268] The process is completely consistent with steps three to four of Embodiment 6 of the present invention, namely, the gel fluid at 74°C is formed in a mold at 67°C (temperature difference of 7°C), frozen for 14.5 hours, vacuum dried for 19 hours, and hydrated for 13.5 hours.

[0269] The artificial meniscus prepared in this comparative model had an elastic modulus of 1.1 MPa, a tensile strength of 3.5 MPa, and an elongation at break of 280% after 10... 6 After several cycles of fatigue testing, the compression modulus decreased by 13%, and the coefficient of friction was 0.165; its microstructure showed localized aggregation of the waterborne polyester (and...). Figure 2 In contrast), uneven entanglement (compared to) Figure 3 (Comparison of molecular weight distribution curves) proves that an imbalanced ratio leads to insufficient contact between bimolecular chains, affecting synergistic performance.

[0270] Comparative Example 8

[0271] Using the same raw materials and process as in Example 7 of this invention, except that the stepwise addition of acetone in step one is changed to a single addition, the specific operation is as follows:

[0272] Step 1: Synthesis of Enhanced Waterborne Polyesters

[0273] Weigh 10g PPG (molecular weight 2200), 12.5g PEG (molecular weight 1200), 6g IPDI and 0.12g stannous octoate, heat to 71℃ and stir at 130r / min for 2.7 hours. After the initial reaction, add 34.5mL acetone at once (total amount is the same as in Example 7), stir evenly and then add 3.2g DMPA. React for 1.3 hours. Then add 2.2mL LTEA and deionized water and stir as in Example 7. Remove acetone by vacuum filtration to obtain a linear aqueous polyester with a number average molecular weight of 9000.

[0274] Steps two through four

[0275] The process is completely consistent with steps two to four of Embodiment 7 of the present invention, namely, mixing 33g of polyvinyl alcohol and 5.5g of waterborne polyester, stirring in steps to prepare a pre-crosslinked fluid, gelling the fluid at 71°C and molding it in a mold at 63°C (temperature difference of 8°C), freezing for 12.5 hours, vacuum drying for 18.2 hours, and hydration for 12.5 hours.

[0276] The artificial meniscus prepared in this comparative example had an elastic modulus of 0.92 MPa, a tensile strength of 3.6 MPa, and an elongation at break of 310%. After 10... 6 After several cycles of fatigue testing, the compressive modulus decreased by 11%, and the coefficient of friction was 0.155; residual solvent testing showed that the acetone residue was 0.03% (compared to...). Figure 4The comparison shows that the acetone content was 0.008% higher than that in Example 7, demonstrating that the stepwise addition of acetone is crucial for precise viscosity control and reducing residue.

[0277] Comparison of examples and embodiments

[0278] Material system Waterborne polyester + polyvinyl alcohol bimolecular entanglement system Single material or dual material but key processes missing / parameters out of control Hybrid process Step-by-step premixing + fine mixing to prevent air bubbles from separating from the phase. One-time mechanical stirring or conventional mixing is prone to defects. Molecular weight control 5000-20000 linear molecules, suitable for entanglement requirements Single high molecular weight or excessively long / cross-linked molecular chains, resulting in ineffective entanglement. Reinforcement process Freeze-dry-hydration closed loop, locking in entangled structures Without reinforcement or with simplified processes, the structure is unstable. Key parameters Strictly control the rate of deionized water addition and molding temperature difference, etc. Parameters out of range or critical parameters out of control

[0279] 2. Performance Comparison

[0280] The elastic modulus of Examples 1-8 of this invention is 0.9-1.2 MPa (highly matched with the original meniscus of 0.8-1.2 MPa), and the elongation at break is 320%-385%, achieving a synergy between strength and elasticity. In contrast, Comparative Example 1 has an excessively high elastic modulus (1.5 MPa) and an elongation at break of only 200%. Comparative Examples 3-8 each exhibit a single defect in mechanical properties or elasticity, failing to meet clinical needs (such as...). Figure 5 The advantages of this invention are evident from the comparison of fatigue stability.

[0281] The embodiments of the present invention have been tested for 10 years. 6 After several fatigue tests, the compression modulus decreased by only 6.8%-10%, and the coefficient of friction remained stable at 0.14-0.15; the decrease rate of comparative examples 1-8 was 11%-30%, and the coefficient of friction was 0.16-0.22, and it continued to increase with the number of cycles (e.g. Figure 6 (Comparison) demonstrates that the bimolecular entanglement system can significantly improve long-term stability.

[0282] The microstructure of this invention embodiment is a uniform and dense entangled network. Figure 2 ), with uniform molecular weight distribution ( Figure 3 ), with extremely low residual solvent content ( Figure 4 The comparative sample exhibited defects such as phase separation, bubbles, cross-linking and aggregation, and excessive residual solvent, which directly affected product performance and biocompatibility.

Claims

1. A method for manufacturing an artificial meniscus, characterized in that, Includes the following steps: Step 1: Synthesis of Enhanced Waterborne Polyesters Polyol, isocyanate and catalyst were placed in a reaction vessel and heated and stirred to react; solvent was added to react with 2,2-dimethylolpropionic acid, and then solvent was added to react with triethylamine; deionized water was added and the stirring speed was adjusted, and finally the solvent was removed to obtain waterborne polyester; Step 2: Preparation of fatigue-resistant hydrogel pre-crosslinked fluid Polyhydroxy alcohol macromolecules are dissolved in deionized water to form a transparent solution, which is then mixed with the aqueous polyester from step one. After premixing, fine mixing, and high-temperature and high-pressure treatment, a pre-crosslinked fluid is obtained. Step 3: Integrated molding of artificial meniscus The pre-crosslinked fluid is heated to form a gel fluid, which is then injected into a preheated mold. After cooling, the pre-formed artificial meniscus is removed. Step 4: Artificial Meniscus Reinforcement The pre-formed artificial meniscus is freeze-dried and hydrated to obtain an enhanced artificial meniscus.

2. The manufacturing method according to claim 1, characterized in that, In step one, the mass ratio of polypropylene glycol (PPG) to polyethylene glycol (PEG) is 1:1.2-1.

5.

3. The manufacturing method according to claim 1, characterized in that, In step one, the peristaltic pump adds deionized water at a rate of 5-10 mL / min.

4. The manufacturing method according to claim 1, characterized in that, In step one, the amount of triethylamine (TEA) added is 2-4 mL.

5. The manufacturing method according to claim 1, characterized in that, In step one, the number-average molecular weight of the polyester molecules is 5000-20000.

6. The manufacturing method according to claim 1, characterized in that, In step two, the stepwise stirring method is as follows: first, the system is placed in an environment of 50~60℃ and mechanically stirred at a speed not exceeding 80r / min.

7. The manufacturing method according to claim 1, characterized in that, In step two, the molecular weight of the polyhydroxy alcohol macromolecular polyvinyl alcohol is 70,000-80,000.

8. The manufacturing method according to claim 1, characterized in that, In step three, the temperature difference between the gel fluid and the meniscus mold is 5~10℃.

9. The manufacturing method according to claim 1, characterized in that, In step three, the pressing pressure of the pressing head device is 0.3-0.5 MPa.

10. An artificial meniscus based on the method of any one of claims 1-9.